Direct measurement of ATP7B peptides is highly effective in the diagnosis of Wilson disease - Collins, Christopher; Yi, Fan; Dayuha, Remwilyn; Duong, Phi; Horslen, Simon; Camarata, Michelle; Coskun, Ayse K.; Houwen, Roderick H. J.; Pop, Tudor L.; Zoller, Heinz; Yoo, Han-wook; Jung, Sung Won; et al. (Gastroenterology, 2021)
Both existing clinical criteria and genetic testing have significant limitations for the diagnosis of Wilson disease (WD), often creating ambiguities in patient identification and leading to delayed diagnosis and ineffective management. ATP7B protein concentration, indicated by direct measurement of surrogate peptides from patient dried blood spot samples, could provide primary evidence of WD.
Gesehen am 07.09.2022